(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Climate change has evolved from an environmental concern into a defining variable of global power politics. The transition toward green technology—renewable energy systems, electric mobility, hydrogen fuel, carbon capture, and critical mineral supply chains—is reshaping the architecture of international relations. This paper examines how technological innovation in climate mitigation has become a strategic instrument of statecraft, influencing global power hierarchies, trade alignments, and diplomatic negotiations. Drawing on a qualitative and policy-analytical approach, the study explores the intersection of green industrial policy, technological competition, and climate diplomacy. It argues that states are increasingly leveraging clean energy leadership not only to meet sustainability goals but also to secure geopolitical influence, economic advantage, and strategic autonomy. The emergence of carbon border adjustments, climate finance mechanisms, and technology-transfer debates illustrates how environmental cooperation is simultaneously a site of rivalry. The paper further analyzes the implications for Global South countries, particularly in terms of access to finance, technology equity, and participation in supply chains for critical minerals. By situating green technology within broader frameworks of international political economy and non-traditional security, the study highlights the dual character of climate diplomacy as both cooperative and competitive. Ultimately, the article contends that the global energy transition is not merely an environmental transformation but a reconfiguration of international power structures, with long-term consequences for global governance, multilateralism, and sustainable development.